Văn Miếu Quốc Tử Giám / Trần Đoàn Lâm - Trần Đoàn Lâm
In the heart of Hanoi, amidst the bustling streets of the capital city of modern-day Vietnam, stands the Van Mieu - Quoc tu Giam (Temple of Literature - school for the sons of the nation), a quite place where scholars come to read, artists come to paint, and travelers come to sekk traces of nearly a thousand years of Vietnamese culture and history.